Le fonctionnement des académies équestres et haras septentrionaux au XVIIIe siècle à partir d’un patrimoine archivistique national et régional - Amandine Jelen (In Situ)
In two northerners “countries of States” recently annexed to the french kingdom, develop equestrian practices supervised by the royal, provincial and/or municipal authorities. Set up and controlled by the Assembly of States, stud farms are established in 1724 for Walloon Flanders and about 1770 for Artois. The academy “to ride to the nobility” is established in Lille at the end of the XVIIth century and continues until 1775. That of Arras knew only a few years of activity between 1753 and 1758. These four equestrian establishments, connected with the various power, generated a rich, varied and often scattered archival heritage.